Estudo fitoquímico e biológico do extrato hidroalcoólico de Inga marginata Willd - Maziero, Maiara (2019)
Medicinal plants have been used since antiquity by man to cure various diseases. Even today, they are widely used by the population in a palliative way, for healing and also associated with conventional medicines. Inga marginata belongs to the family Fabaceae, genus Inga, has several popular nomenclatures such as ingá and ingá-mirim is a leguminous plant, with a wide distribution in Latin America. It has antidiarrheal, antimicrobial, antinociceptive, anti- inflammatory properties, among others. The objective of the present work was to obtain the crude extract of the leaves of I. marginata by the maceration process, perform phytochemical characterization, identify and quantify compounds present in the extract, evaluate biological activities, such as antinociceptive and antimicrobial activity, as well as evaluate cytotoxicity, genotoxicity and antioxidant potential against reactive oxygen and nitrogen species. From the phytochemical characterization of I. marginata, the following concentrations were found: 110.60; 100.38 and 27.04 mg/g for total polyphenols, flavonoids and tannins, respectively. Using HPLC, the following compounds were identified and quantified as gallic acid (1,837 mg/g), epicatechin (22.493 mg/g) and rutin (5.217 mg/g). The hydroalcoholic extract did not present cytotoxicity and genotoxicity. The high antioxidant power of the extract was demonstrated by means of antioxidant tests (DPPH – IC50 17,306 μg/mL; DCFH - DA - 10 and 60 μg/mL; ORAC - 2952,944 μmol Trolox/g and nitric oxide - 15 μg/mL) under analysis. The antimicrobial activity was evaluated against bacterial strains of Staphylococcus aureus, Bacillus cereus, Enterobacter aerogenes, Staphylococcus epidermidis, Micrococcus luteus, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Salmonella and Pseudomonas aeruginosa. The best results were obtained for S. epidermidis (128 μg mL), S. aureus (128 μg/mL), M. luteus (256 μg/mL) and K. pneumoniae (256 μg/mL). The antinociceptive evaluation also showed promising results, with a concentration of 100 mg/kg more effective. Thus, due to the favorable results, it is possible to suggest the use of I. marginata in a safe and effective way.